1998
DOI: 10.1111/1467-9566.00081
|View full text |Cite
|
Sign up to set email alerts
|

Doing Nothing is No Choice: Lay Constructions of Treatment Decision‐making Among Women with Early‐stage Breast Cancer

Abstract: Open-ended personal interviews were conducted with 20 women with early stage breast cancer attending a regional cancer centre in Southwestern Ontario. We explored three related issues: (1) the extent to which these women perceived that they had treatment options; (2) their understanding of treatment benefits and risks; and (3) the role they wanted for themselves and their oncologists in treatment decision-making. We found, first, that many women who were presented with the choice to undergo some form of adjuva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
104
0
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 26 publications
7
104
0
6
Order By: Relevance
“…Thus, when stating that they have not perceived a treatment choice, patients may mean other things besides being offered choice of treatment by their doctor. These results are in agreement with the observations by Charles et al (1998), who describe in a qualitative study that many women were preoccupied with avoiding the possibility of disease recurrence. For this reason, these women believed that the only decision they could make was to accept the treatment that was offered.…”
Section: Discussion Perception Of (No) Treatment Choicesupporting
confidence: 93%
“…Thus, when stating that they have not perceived a treatment choice, patients may mean other things besides being offered choice of treatment by their doctor. These results are in agreement with the observations by Charles et al (1998), who describe in a qualitative study that many women were preoccupied with avoiding the possibility of disease recurrence. For this reason, these women believed that the only decision they could make was to accept the treatment that was offered.…”
Section: Discussion Perception Of (No) Treatment Choicesupporting
confidence: 93%
“…For patients and physicians, choosing an active treatment option, that is, palliative chemotherapy, seems obvious. Best supportive care is often perceived as 'doing nothing' (Charles et al, 1998). For medical oncologists, the patient's wish is an important determinant of their own preference for treatment (Charles et al, 1998;Koedoot et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Best supportive care is often perceived as 'doing nothing' (Charles et al, 1998). For medical oncologists, the patient's wish is an important determinant of their own preference for treatment (Charles et al, 1998;Koedoot et al, 2002). Moreover, they also prefer to 'do something', that is, offering chemotherapy, rather than offering best supportive care (de Haes and Koedoot, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…488,489 Much of the literature examining trial participation has identified altruism, trust in recruiting clinicians and an expectation of personal benefit as the main motivations for participation in trials. 490,491 However, altruism may be overstated as a motivation for participants, and a small but increasing number of studies using qualitative methods to examine the perspectives of clinical trial participants [484][485][486] have concluded that patients participate in a clinical trial because they believe that they are receiving personalised care. One study 486 found that, even when participants recalled the involvement of chance, most also held other coexisting (and sometimes contradictory) views about how and why they had been allocated to the treatment or intervention and believed that they would receive the best treatment for them.…”
Section: Patient and Public Involvementmentioning
confidence: 99%
“…Similarly, a number of studies have identified that personal benefits, hope, access to the most effective treatment, 492 and the enthusiasm and hopes of family and friends were often the driving force behind and key motivations for participation. 490 Such beliefs highlight the vulnerability of some groups and the risks that they are willing to take if there is a chance of survival, 493 and this may be an important factor for trials involving potentially disease course-modifying treatments.…”
Section: Patient and Public Involvementmentioning
confidence: 99%